DC sputtered amorphous In–Sn–Zn–O thin-film transistors: Electrical properties and stability. (February 2016) - Nakata, Mitsuru; Zhao, Chumin; Kanicki, Jerzy
Highlights: An analytical field-effect mobility model is proposed for dc sputtered a-ITZO TFTs. Device characteristics are extracted using both a least square error linear fitting method and a second derivative method. The a-ITZO film thickness and oxygen gas flow ratio are optimized. The oxygen gas flow ratio influences both device characteristics and stability of a-ITZO TFTs. Improved electrical stability is achieved for a-ITZO TFTs in comparison to that of a-IGZO TFTs. Abstract: In this study, we investigated the electrical properties of DC sputtered amorphous In–Sn–Zn–O (a-ITZO) thin-film transistors (TFTs) fabricated under various process conditions. Fabricated a-ITZO TFTs achieved a threshold voltage ( V T ) of 1.0 V, subthreshold swing ( SS ) of 0.38 V/dec and field-effect mobility ( μ eff ) of around 30 cm 2 /V s. An analytical field-effect mobility model is proposed for a-ITZO TFTs with key parameters extracted using different methods. The impacts of a-ITZO channel thickness and oxygen gas flow ratio on device performance were evaluated. Finally, the a-ITZO TFT bias-temperature stress (BTS) induced electrical instability was studied. In comparison to amorphous In–Ga–Zn–O (a-IGZO) TFTs, improved electrical stability was observed for a-ITZO TFTs using exactly the same BTS conditions.